Gallbladder carcinoma with liver metastasis.: Twenty-years survival - Suiffet, Walter (Cirugía del Uruguay, 1976)
This paper presents an interesting case of carcinoma of the gall bladder. There was lithiasis of the gall bladder, smal! adenocarcinoma in the. mucous area, liver metastasis near the bladder 7-8 mm in size. Evolution was favourable with a 20-year survival.